2021
DOI: 10.3390/pharmaceutics13070921
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microplastic in Human Placenta and Meconium in a Clinical Setting

Abstract: Environmental pollution with microplastics (MPs) is a major and worldwide concern. Involuntary exposure to MPs by ingestion or inhalation is unavoidable. The effects on human health are still under debate, while in animals, cellular MP translocation and subsequent deleterious effects were shown. First reports indicate a potential intrauterine exposure with MPs, yet readouts are prone to contamination. Method: To establish a thorough protocol for the detection of MPs in human placenta and fetal meconium in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
157
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(162 citation statements)
references
References 33 publications
3
157
1
1
Order By: Relevance
“…It is also found in co-lectomy samples [32], saliva, the surface of skins, and head hair [33]. Recently, microplastics were also detected in human placenta [34,35] and lung tissue [36], providing evidence for microplastic penetration and incorporation in the human tissue.…”
Section: Introductionmentioning
confidence: 94%
“…It is also found in co-lectomy samples [32], saliva, the surface of skins, and head hair [33]. Recently, microplastics were also detected in human placenta [34,35] and lung tissue [36], providing evidence for microplastic penetration and incorporation in the human tissue.…”
Section: Introductionmentioning
confidence: 94%
“…However, the route of NMP transfer into the body, into the bloodstream, and then into the placenta is unknown. Braun et al (2021) detected microplastics >50 lm in the placenta and meconium after cesarean, while emphasizing the need for researchers to carefully evaluate the potential for contamination of samples from air fallout. Research suggests that the degree of particle transfer across the placenta changes across the trimesters with increasing gestational age (Vähäkangas and Myllynen 2009).…”
Section: Exposure Routesmentioning
confidence: 99%
“…Recently, microplastics were discovered in human placenta (Ragusa et al 2021), meconium, and infant stool (Zhang et al 2021;Schwabl et al 2019;Braun et al 2021). Yet the impacts of exposure to plastic particles during early windows of vulnerability are almost entirely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study, 12 polypropylene (PP) particles, 5–10 µm in size, were found in four placentae from vaginal deliveries [ 161 ]. In the second, larger microparticles > 50 µm of three plastics, polyethylene (PE), polypropylene (PP), and polystyrene (PS) were found in human placenta and meconium from caesarean delivery [ 162 ]. The location of microplastics on the foetal side of the placenta suggests that the placental barrier had been compromised by microplastics, even though transfer to the foetus has not been demonstrated.…”
Section: Natural and Synthetic Materialsmentioning
confidence: 99%